Readability of word problems in certain mathematics textbooks used in Quezon City public schools for 1971-72 - Galinato, Leticia B. 1946- ([Quezon City s.n.], 1974)
The aim of this study was to analyze the word problems found in the sixth grade textbooks and achievement tests of Quezon City public schools for the school year 1971-1972. It sought to determine whether they have a readability level that is suitable for the intended grade level.
Thesis (M.A.T. Elementary Mathematics)--University of the Philippines.
Keywords: Mathematics -- Textbooks -- Philippines